Correction of Physiological Artifacts in Multi-Echo fMRI Data-Evaluation of Possible RETROICOR Implementations - Kovářová, Anežka; Mikl, Michal (Human brain mapping, 2025)
The study evaluates the efficacy of RETROICOR (Retrospective Image Correction) in mitigating physiological artifacts within multi-echo (ME) fMRI data. Two RETROICOR implementations were compared: applying corrections to individual echoes (RTC_ind) versus composite multi-echo data (RTC_comp). Data from 50 healthy participants were collected using diverse acquisition parameters, including multiband acceleration factors and varying flip angles, on a Siemens Prisma 3T scanner. Key metrics such as temporal signal-to-noise ratio (tSNR), signal fluctuation sensitivity (SFS), and variance of residuals demonstrated improved data quality in both RETROICOR models, particularly in moderately accelerated runs (multiband factors 4 and 6) with lower flip angles (45°). Differences between RTC_ind and RTC_comp were minimal, suggesting both methods are viable for practical applications. While the highest acceleration (multiband factor 8) degraded data quality, RETROICOR's compatibility with faster acquisition sequences was confirmed. These findings underscore the importance of optimizing acquisition parameters and noise correction techniques for reliable fMRI investigations.
Keywords: Magnetic Resonance Imaging; mozek; magnetická rezonanční tomografie; Humans; mapování mozku; multi‐echo; Female; mladý dospělý; dospělí; Artifacts; artefakty; lidé; denoising; počítačové zpracování obrazu; Image Processing, Computer-Assisted; fMRI; poměr signál - šum; Brain Mapping; Adult; Signal-To-Noise Ratio; ženské pohlaví; Male; RETROICOR; Brain; Young Adult; mužské pohlaví